Análise do ensino inclusivo de alunos surdos nas aulas de Química em uma escola da rede estadual do município de Ananindeua - PA - RODRIGUES, Carlos Eduardo Conceição (2020)
The development of this research arose from the need to verify the effectiveness of inclusive education offered by a state school in the municipality of Ananindeua. To this end, we sought to conduct an analysis of this inclusive education for deaf students, during chemistry classes. Thus, it was necessary to know the reality of inclusive education, to identify the main methodologies adopted by teachers during their teaching and evaluation and to know the main difficulties faced by teachers and students during the teaching and learning process. For that, we used the qualitative method, where observations were used, together with the application of questionnaires for teachers and deaf students as a data collection technique, which was carried out in the period from 18 to 29 November 2019. In view of this, it was found that basic aspects necessary for the development of inclusive education are being offered, but it is worth directing a look at the training of teachers, given that it was found that these teachers working in the area do not have specific training.